ANALYSIS OF SPATIAL MANAGEMENT IN REGIONAL DEVELOPMENT PLANNING (CASE STUDY: MEDAN CITY) - Muhammad Alfikri Matondang (JURNAL GEOGRAFI, 2022)
Spatial planning is an area pattern created or built based on planning, aiming to develop a sustainable spatial design. This study aims to analyze the spatial way of Medan City and its relation to regional development planning. This study uses an empirical juridical method using data from government agencies and literature studies. The results of this study include Medan City spatial planning is regulated in Medan City Regional Regulation No. 13 of 2011 concerning Medan City's regional spatial plan for 2011-2031 and Medan City's Regional Regulation No. 2 of 2015 regarding detailed spatial planning and Medan City zoning regulations for 2015-2035. Spatial planning depends on structural components and space utilization patterns arranged in spatial planning. Spatial planning in Medan City cannot be equated with other cities. The future spatial planning policy is a public policy that must be transparent and fair and accommodate the interests of various levels of society so that the community's involvement as development actors in the planning, utilization, and control of space is necessary. Spatial management in the city of Medan must combine structural and non-structural so that the city's objectives will achieve spatial planning.Keywords: Spatial Planning, Planning, Regional Development, Medan City